(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
This article is based on the story of a work experience within the framework of the extension project "Education and Promotion of Rights in the José Luis Cabezas neighborhood of Ensenada" (FaHCE-UNLP). It consisted of a photography workshop focused on the environment, through which different activities were developed with children and adolescents from the neighborhood. From there, the article seeks to highlight two dimensions that cross the extension work in our team. On the one hand, a methodological strategy that starts from recovering and valuing the knowledge and practices of children and adolescents. On the other hand, a perspective "from below”, that, as part of the territory, takes on full meaning in and for its inhabitants. It is concluded that the workshop, oriented by the promotion of access to rights, it strengthened the conception of the environment as an amalgam between the natural and the built.